Comercio formal e informal en el sector de la media luna y su influecia en el desarrollo socio-económico - Gabriel Sebastián, Vallejo Méndez (2019)
Due to the demographic growth in the sector called “Media Luna.” The increase of formal and informal trade in that area has been evident. People who in their daily lives have been selling products and services of all kind such as food products even technological products and services. Also mechanical services, as well as esthetics and maintenance services, have allowed activating to the economy in this sector. It is why the importance of this research project, which intends to diagnose in a general way, the main activities of formal and informal trade in the sector called “Media Luna.”; With the primary intention of knowing the impact generated by these and also proposes trade strategies that benefit the socio economic development of the mentioned sector.